2019
DOI: 10.1126/science.aav2334
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-arc diversity on surface terminations of the magnetic Weyl semimetal Co 3 Sn 2 S 2

Abstract: contributionsBulk-surface correspondence in Weyl semimetals assures the formation of topological "Fermi-arc" surface bands whose existence is guaranteed by bulk Weyl nodes. By investigating three distinct surface terminations of the ferromagnetic semimetal Co 3 Sn 2 S 2 we verify spectroscopically its classification as a time reversal symmetry broken Weyl semimetal. We show that the distinct surface potentials imposed by three different terminations modify the Fermi-arc contour and Weyl node connectivity. On t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
359
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 586 publications
(373 citation statements)
references
References 40 publications
11
359
0
3
Order By: Relevance
“…More recent calculations and measurements including ARPES and STM show that Co 3 Sn 2 S 2 is a WSM, with Weyl points located ∼ 60 meV above the Fermi energy [4,5]. However, the magnetic order is not straight forward, and several studies have recently suggested this material hosts a more complex magnetic texture.…”
Section: Introductionmentioning
confidence: 99%
“…More recent calculations and measurements including ARPES and STM show that Co 3 Sn 2 S 2 is a WSM, with Weyl points located ∼ 60 meV above the Fermi energy [4,5]. However, the magnetic order is not straight forward, and several studies have recently suggested this material hosts a more complex magnetic texture.…”
Section: Introductionmentioning
confidence: 99%
“…13 The layered Shandite compound Co3Sn2S2 is one of the very few known magnetic Weyl semimetals. [14][15][16] Apart from its interesting topological properties, this compound is also investigated for its thermoelectric properties and possible skyrmionic phase. 17 The topological effect evoked by the Weyl points is responsible for the giant anomalous Hall effect in this compound.…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, the Weyl nodes are projected onto the different points in the surface Brillouin zone. Although the Fermi arcs are topologically protected, their shape depends on the boundary conditions . Therefore, it is interesting what happens with the Fermi arc states if the surface is still parallel to the chiral shift but is, however, curved.…”
Section: Introductionmentioning
confidence: 99%